Changes of Physical Properties of Sandy Soil And Growth of Physic Nut (Jatropha Curcas L.) Due to Addition of Clay and Organic Matter - Djajadi, Djajadi; Heliyanto, Bambang; Hidayah, Nurul (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
Agricultural sandy soil in Situbondo, East Java province, Indonesia which is used as a center garden for physic nut seed production has poor physical properties of soil indicated by low capacity to retain water. For plant growth of physic nut, the sandy soil physical properties need to be improved. In this study, the influence of addition of clay together with organic matter and intervals of irrigation to sandy soil on aggregate stability, bulk density, total soil porosity, water available content and plant growth of physic nut was investigated. The rates of clay and organic matter incorporated to top sandy soil were 5% clay + 0.8% organic matter and 1O% clay + 1.6% organic matter. Two intervals of irrigation tested were 10 days and 20 days. The results showed that incorporation of clay together with organic matter increased aggregate stability, total soil porosity, available water content and plant growth of physic nut. Intervals of irrigation had no influence of soil physical properties and plant growth.Keywords: agricultural, sandy soil, clay, organic matter, soil properties, physic nut